2016
DOI: 10.1111/nhs.12219
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between gastrointestinal symptoms, uncertainty, and perceived recovery in patients with gastric cancer after gastrectomy

Abstract: This study examines relationships between gastrointestinal symptoms, uncertainty, and perceived recovery in gastric cancer patients after gastrectomy. Data were collected from 146 patients at an outpatient clinic of a university hospital in Seoul, Korea from October to November 2012. The Gastrointestinal Symptoms Rating Scale, the Mishel Uncertainty in Illness Scale, and questions on perceived recovery of physical, psychological, and social functions were analyzed. High gastrointestinal symptom scores were rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
(56 reference statements)
1
20
0
3
Order By: Relevance
“…In the setting of gastric malignancies, other reasons have been advocated, including (1) the detection of adverse effects of a previous surgery, such as vitamin and iron depletion or malnutrition or digestive sequelae[9]; (2) the collection of data to evaluate the efficacy and outcomes of treatments; and (3) the detection of psychological and/or social problems subsequent to the disease and the provision of appropriate support to the patients[10]. …”
Section: Rationale Of Follow-upmentioning
confidence: 99%
“…In the setting of gastric malignancies, other reasons have been advocated, including (1) the detection of adverse effects of a previous surgery, such as vitamin and iron depletion or malnutrition or digestive sequelae[9]; (2) the collection of data to evaluate the efficacy and outcomes of treatments; and (3) the detection of psychological and/or social problems subsequent to the disease and the provision of appropriate support to the patients[10]. …”
Section: Rationale Of Follow-upmentioning
confidence: 99%
“…17 The population of the studies consisted of patients with the following cancers: breast, prostate, gastro intestinal tract, ovary and other gynecological cancers. 8,[12][13][14][15][16] Regarding sociodemographic and clinical aspects of the studies, half of the population consisted of females. In general, the average age of the population ranged between 21-86 years.…”
Section: Resultsmentioning
confidence: 99%
“…One of the studies (n.6) demonstrated that patients with schooling corresponding to secondary education or less presented higher levels of uncertainty. 16 In half of the articles, the populations had higher education, the other party represented the primary schooling or less years of schooling. Populations with a lower monthly income also showed higher levels of uncertainty.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpreting the framework of stimuli and elaborating the meaning of what happens makes it easier for the person to structure a scheme that creates less uncertainty. [20][21] Providing people with proper levels of information, involving them in making decisions according to their level of commitment and discussing present and/or future care according to their needs contributes so that health personnel can individualize the care for these people. 22 Nevertheless, as a result of the way the medical staff communicates the diagnosis, it is perceived as imminent death, generating uncertainty.…”
Section: Discussionmentioning
confidence: 99%